News Value dalam Konstruksi Berita Media Massa Lokal: Studi Fenomenologi tentang Penggunaan News Value dalam Konstruksi Berita pada Koran Harian Radar Jember: News Value in the Construction of Local Mass Media News: A Phenomenological Study on the Use of News Value in News Construction at the Daily Newspaper Radar Jember - Kun Wazis (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2012)
The strength of mass media is determined by the quality of news. The quality of news is influenced by the news value set by the mass media. Similarly, the strength of local mass media depends on the news value used in constructing the news. Moreover, news construction serves as a stake for the media in providing market appeal. Some elements of news value, such as freshness, uniqueness, drama, actuality, proximity, magnitude, controversy, figures, exclusivity, and mission, become standards in judging whether an event is worth reporting. Journalists, editors, managing editors, and editors-in-chief have their own styles in applying news value in news construction. Based on this study, it is concluded that: reporters, editors, managing editors, and editors-in-chief of Radar Jember apply the news value taken from Java Pos as the main media, referred to as the